Engineering E. coli recombinant strains for high yield production of Burkholderia pseudomallei specific antigens - Yu. A. Kuzyutina (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
A risk of introducing into the Russian Federation exotic infections including laboratory-confirmed melioidosis regularly recorded worldwide necessitates development and improvement of express diagnostics tools. Cross reactivity between phylogenetically related species of the genus Burkholderia complicates melioidosis diagnostics by express test methods based on using monoclonal antibodies against pathogen exopolysaccharide epitopes. Searching for target antigens to create the next generation group- and species-specific immunodiagnostic reagents for identifying Burkholderia pseudomallei is still of high priority. The study was aimed at cloning complete coding sequences for cell surface proteins differentiating  Burkholderia pseudomallei and optimizing recombinant antigens purification protocol. In silico comparative study allowed to select highly immunogenic B. pseudomallei outer membrane proteins Omp38 and OmpA/МotB as target biomolecules. For cloning, omp38 and ompA/motB gene-specific amplicons were obtained by PCR and ligated with the linear expression vector RIC-Ready pPAL7. Competent E. coli C-Max5α cells were transformed by a ligation mixture for producing recombinant plasmids, which were further purified to transform E. coli BL21 (DE3) cells for robust recombinant protein expression. Due to a potential multimeric protein structure, a standard protein purification protocol from native cell lysate was inefficient, which was modified to increase recombinant protein yield. However, by adding denaturing conditions at intermediate purification steps caused hydrolysis of peptide bonds in the target proteins, presumably between proline and asparagine residues. As a result, N-terminal fragments connecting recombinant proteins to the stationary phase of chromatographic column were eluted and evaluated for linear epitope detection according to their molecular weights. In silico analysis data identified highly antigenic motifs within the polypeptides studied. Thus, strains of E. coli BL21(DE3) BpsOmp39 and E. coli BL21(DE3) BpsOmpА engineered by us produce cell surface proteins Omp38 and ОmpA/МotB derived from melioidosis pathogen, which can be useful for developing diagnostic test systems.